A comparative study on ultrasound vs splinting in firstCarpometacarpal (cmc) joint osteoarthritisIn geriatric population - DR. TUSHAR J PALEKAR,; JANAKI R BANPEL, (International Journal of Pharma and Bio Sciences, 2017)
Osteoarthritis of first carpometacarpal joint is common in geriatrics. There is lack of evidence to support non-surgical interventions as low clinical trials were conducted. 30 individuals were taken with first carpometacarpal joint osteoarthritis, divided in 2 groups of 15 each. Thumb grinding test was performed to confirm diagnosis. Group A was given ultrasound and Group B was given splinting (thumb spica). Pain and range of motion was assessed using Numerical Pain Rating Scale and finger Goniometer.There was a significant difference in pain and range of motion in both groups post treatment, but highly significant difference in pain reduction was seen in group A (ultrasound group). Non thermal effects of ultrasound prove beneficial and night splinting helps rest the inflamed arthritic joint not interfering with day use of hand. Study concludes that ultrasound helps in alleviation of pain and improves functional measures although splinting should be used as an adjunct.